IMPLEMENTATION OF CHARACTER EDUCATION THROUGH A HUMANIST APPROACH IN SKI LEARNING AT MTS NURUS SALAM - Muhammad Rahim; Khairuddin Lubis (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2026)
Love-based curriculum (KBC) as a curriculum design that focuses on character development towards Golden Indonesia 2045. Character development can be done with a humanist approach in learning. The humanistic approach makes learning more meaningful and humanistic, because it emphasizes the real experiences of students. This study aims to describe the humanistic approach in Islamic Cultural History (SKI) lessons at MTs Nurus Salam Deli Tua, Deli Serdang. This research is qualitative descriptive related to the humanistic approach to SKI lessons at MTs Nurus Salam Deli Tua Deli Serdang. Data were collected by observation and observation, interviews and document studies. Penganalisaan data melalui reduksi, penyajian data dan penarikan kesimpulan. The results of the study show that the humanistic approach in SKI learning is carried out by internalizing the material with the knowledge and experience of students, so as to increase understanding and awareness of human status and equality, mutual respect (tolerance), responsibility and improve critical thinking skills. Through a humanistic approach, SKI learning is centered on students by involving students in participating and demonstrating activeness.